Incidence and management of intraocular lens opacification after primary phacovitrectomy for combined cataract and diabetic vitrectomy - Mohammed A. Al-Naimy; Marwa A. Khairy; Ahmed Roshdy Alagorie; Yasmine A. Deiaeldin (Journal of the Egyptian Ophthalmological Society)
Purpose To evaluate the incidence, risks, and sequelae of hydrophobic versus hydrophilic intraocular lens (IOL) opacification in diabetic patient’s undergone primary phacovitrectomy, and suggest the best management plan for IOL opacification. Patients and methods This retrospective study included 42 eyes of 42 diabetic patients scheduled for primary combined phacoemulsification and pars plana vitrectomy in Alpha vision center in the period from July 2021 to November 2022 for significant cataract and any cause that indicates pars plana vitrectomy in diabetic patients like unresolved vitreous hemorrhage, traction retinal detachment, combined traction rhegmatogenous retinal detachment, subhyaloid hemorrhage, and epiretinal membranes or combination of these pathologies. Hydrophilic IOLs were implanted in half patients while hydrophobic IOLs were implanted in the other half. All patients were followed up for their primary retinal pathology and for monitoring the incidence and progression of any IOL opacification. Patients who developed IOL opacification were examined for its visual impact and those who needed IOL exchange were scheduled for another surgery. Surgical details of the second intervention and any adverse events were recorded. Results Seven (33.3%) cases in hydrophilic group developed IOL opacification while no cases developed opacification in hydrophobic group (P=0.009). Five patients with IOL opacification required IOL exchange, with either secondary implantation of sulcus three pieces IOL or iris claw that resulted in significant improvement of patient’s vision. One patient of those undergone IOL exchange developed progressive secondary neovascular glaucoma. A statistically significant association between diabetic control and the level of glycosylated hemoglobin and the development of IOL opacification in hydrophilic group was noticed. Conclusion Diabetic patients who require primary phacovitrectomy have higher incidence of hydrophilic IOL opacification that may affect their vision and the sequelae of IOL exchange is considerable. So, it is recommended to use hydrophobic IOL in these patients. Tight glycemic control post diabetic vitrectomy may play a role in preventing the IOL opacification especially in implanted hydrophilic IOLs.